DSM-5: Seven years later- developments and challenges in the classification of mental disorders - Christopoulou, Anna; Gkirlemi, Aria; Apostolidou, Anna; Stefanou, Electra; Koutoumatsioti, Anastasia; Marouli, Elizabeth; Fotinou, Maria; Ermiliou, Vasiliki; Koutrias, Apostolos; Ntali, Evdokia (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The DSM-5, the fifth publication of the diagnostic system DSM (Diagnostic and Statistical Manual of Mental Disorders) has been a source of intense scientific interest and debate. The purpose of this article is to review the most important developments in this scientific dialogue during the seven years after the publication of the manual. To begin with, reference is briefly made to the development of the DSM-5 as well as to criticism and response to this criticism that immediately followed publication of the manual. Then, later developments regarding the DSM-5 are discussed, such as the focus on particular issues of concern as well as significant social and economic changes regarding contemporary classification systems. Research findings on the current use of diagnostic classification systems are also presented. Finally, particular areas of interest and concern regarding future classification, and new proposals as the Research Domain Criteria (RDoc) of the National Institute of Mental Health in the United States are discussed.